FACTORS INFLUENCING THE SUCCESS OF CHARACTER EDUCATION IN SMP N 2 RANAH BATAHAN DISTRICT PASAMAN BARAT REGION - Doanta, Nepra; Drs. Edi Suarto, M.Pd, Drs. Edi Suarto, M.Pd; SE, M.Si, Nefilinda (Pendidikan Geografi, 2014)
ABSTRACT This research aims to the factors that influence the success of character education in SMP N 2 Ranah Batahan Pasaman Barat District views from: family, school and community environments.This research is a descriptive correlational. Population are all students of class VII and class VIII SMP N 2 Ranah Batahan Pasaman Barat District at 2013 comprised of 8 local numbering 254 people, samples were taken with a proportional random sampling technique with proportion 40% so sample of 102 students.The results of the study found that : 1) There is influence of family environment on the success of character education in SMP 2 Ranah Batahan Pasaman Barat District because of t count > t table ( 7,157 > 1,662 ), the effects were moderate ( r = 0,582 ) and a small contribution ( 33,9 %), (2) There is influence a school of environmental on the success of character education in SMP N 2 Ranah Batahan Pasaman Barat District because of t count > t table ( 5,237 > 1,662), the effects were moderate (r = 0,464) with a small contribution (21,5%), (3) There are influence environmental on the success of character education community at SMP N 2 Ranah Batahan Pasaman Barat District because of t count > t table (3,081 > 1,662), the effect is low ( r = 0,294) with a very small contribution (8,7 % ) and (4) there is a significant and positive influence of family, school and community environments together towards the success of character education in SMP N 2 Ranah Batahan Pasaman Barat District because of F count > F table (29,417 > 2,712). The effect of three variables on the success of character education in SMP N Ranah Batahan Pasaman Barat District categorized as moderate (r = 0,688) and a significant contribution (47,4%)